Management of amnestic and behavioral disorders after ketamine anesthesia - Belenichev, I. F.; Burlaka, B.; Puzyrenko, A.; Ryzhenko, O.; Kurochkin, M.; Yusuf, J.; Бєленічев, Ігор Федорович; Бурлака, Богдан Сергійович; Курочкін, Михайло Юрійович (My University, 2019)
General anesthesia may cause damage of the central nervous system and cognitive dysfunction in the postoperative period. A new intranasal form of Noopept (N-Phenylacetyl-L-prolylglycine ethyl ester) was developed by our team at the Department of the medical technology (Zaporizhzhia State Medical University, Ukraine). The objectives of this investigation were the study of neuroprotective action of Noopept and to prove using in the clinic for correction of amnestic and behavioral disorders after ketamine anesthesia. We discovered that the intranasal administration of noopept after ketamine anesthesia significantly decreases anxiety and excitability, raises the animal’s activity, shows an intensive antiamnesic effects and increases animal’s training ability. Noopept significantly exceeds piracetam and cerebrocurin according to neuroprotective effects.
Keywords: ketamine; N-Phenylacetyl-L-prolylglycine ethyl ester; noopept; cerebrocurin; piracetam; neuroprotection